Media Dan Hak Asasi Manusia: Pencegahan Pengaruh Negatif Media Televisi Terhadap Anak - Nabila Amanda Pulungan; Alya Rachma; Reh Bungana Beru; Maulana Ibrahim (Hakim, 2024)
This research aims to find out how to prevent the negative influence of television media on children based on the implementation of child protection laws. The type of research that the author conducted was descriptive research in the form of a literature study. Based on the research results, it shows that the implementation of child protection laws is very important for protecting children's rights. Child protection is not only the responsibility of parents, but also the responsibility of the state, government, society and family. Television media also plays an important role in providing information to children. Be selective in providing information from television media to keep children safe, both physically and mentally